Fermentation Characteristics and Nitrogen Retention of Madura Cattle Fed Complete Rations Containing Soybean Pod and By-Products - Komang Gede Wiryawan; Arief Saefudin; Asnath Maria Fuah; Rudi Priyanto; Lilis Khotijah; Sri Suharti (Faculty of Animal Science, Bogor Agricultural University, 2017)
This study was aimed to evaluate the effect of complete rations containing soybean pod and soybean by-products (soybean meal and tofu waste) on rumen microbial population, fermentation characteristics, nutrient digestibility, and nitrogen retention of Madura cattle. Twelve Madura cattle of 1.5 years of age were given 4 feeding treatments in triplicates in randomized block design experiment. The treatments included T0 (100% native grass) as a negative control, T1 (concentrate: grass (60:40) as a positive control, T2 (complete ration containing 15% soybean pods), and T3 (complete ration containing 30% soybean pods). The treatments were based on feeding practices commonly applied by farmers in the village. The results showed that the use of concentrate rations or complete rations containing soybean pod and by-product did not affect protozoa population, ammonia concentration, and total VFA production compared to cattle fed 100% native grass. In contrast, the use of concentrate rations or complete rations containing soybean pod and by-products reduced acetate and increased butyrate proportion compared to native grass. The use of a concentrate ration resulted the highest propionate proportion. Methane estimation increased with the use of concentrate ration or complete ration containing 15% soybean pod, but it decreased when the level of soybean pod was increased to 30%. It can be concluded that soybean pod has a potential to be used as a fiber source in beef cattle ration to substitute native grass.